The politics of institutional neutrality: ambiguity, fear, and the effort to silence higher education in the USA - Brewer, Curtis; Young, Michelle D. (Frontiers in Education, 2025)
In this paper, we use critical policy analysis to examine the strategy of institutional neutrality and its relationship to the longstanding agenda of US conservatives to limit the societal and political influence of higher education within society. Specifically, we posit that policy ambiguity creates fertile ground for fear-based narratives to shape institutional meaning making and steer policy direction. As Stone, a political theorist, pointed out, ambiguity is an inherent part of political decision-making because policy goals, problems, and solutions are open to multiple interpretations. We examine ambiguity surrounding institutional neutrality for higher education institutions, interrogating its contours, functions, and implications. Drawing on Giroux's concept of the disimagination machine and scholarship on the politics of fear, we examine how political actors have reframed the public's thoughts about higher education and attitudes toward their proper role in society. As part of this analysis, we investigate the role of fear in the recent widespread adoption of institutional neutrality policies by universities across the U.S. and critically engage the range of critiques of institutional neutrality as an organizational strategy for higher education institutions. We conclude with a discussion of alternatives to institutional neutrality and their relationship to academic‘freedom.